PHARMACOGNOSTICAL, PHARMACOLOGICAL AND TRADITIONAL PERSPECTIVES OF APIUM GRAVEOLENS: AN ETHNOMEDICINAL PLANT: Pharmaceutical Science-Pharmacognosy - GUPTA, JITENDRA; GUPTA, REENA; MATHUR, KANCHAN (International Journal of Life Science and Pharma Research, 2019)
Apium graveolens (Hindi name: Celery) belongs to family Apiaceae of order Apiale and is a biennial plant. It is about 25-250 cm in height and found in western Uttar Pradesh, north-western Haryana, Punjab, Himalayas and in some parts of Europe. Fourocoumarin, coumarin and phenols are main categories of phytoconstituents present in it. Celerin, bergaten, aiumoside, aimuetin, aigravin, osthenol, seselin are the main active phytoconstituents of active constituents. Different parts of the plant have various medicinal applications such as antibacterial activity, cardiovascular activity, antidiabetic activity, anti-depressant activity, hypolipidemic effect, effect on kidney, effects on male hormones, spermatogenesis and cytoprotective activity etc. The present review aims at the exploration of pharmacognostical, phytochemical and pharmacological studies of celery. Finally, the review concludes that this would be significantly and scientifically useful for both professional of academia and pharmaceutical industry those are doing research on this plant.